Experimental study on coal seam permeability enhancement and CO2 permeability caused by supercritical CO2 - Yu, Yongjiang; Liu, Jingjing; Yang, Yuntao; Wu, Di; Zhai, Wenbo; Miao, Feng (Frontiers in Earth Science, 2023)
Permeability is one of the most important parameters for characterizing fluid flow and production from reservoirs. In this paper, experimental studies on the percolation, permeation and adsorption of supercritical CO2 in coal seams were carried out, taking into account the effects of injection pressure and temperature, comparing the changes in longitudinal wave velocity of specimens before and after the tests, and analyzing the permeation effect of supercritical CO2 on raw coal specimens. The test results show that when the volume stress is 36 MPa, the permeability of supercritical CO2 in coal increases by 93% on average compared with that of CO2. The modified d-r model was used to fit the adsorption data, and it was found that the excess adsorption capacity of supercritical CO2 by coal decreased with the increase of pressure, and the maximum value was around 8 MPa. When the temperature increased by 10 ℃, the adsorption capacity decreased by 8.3% on average. In the subcritical state of CO2, the changing trend of excess CO2 adsorption in coal is consistent with that of absolute adsorption, which is 16% higher than that of excess adsorption on average. After the action of supercritical CO2, the propagation velocity of the longitudinal wave in the sample decreases significantly, indicating that supercritical CO2 can effectively promote the development of pores and fractures in the coal sample, and has an obvious anti-reflection effect on the coal seam, with the best permeation enhancement effect at 35℃.